SWOT Analysis of Purse Seine Fishery Business : In Laha Village, Ambon City - Andi Taufan (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2023)
Objectives - Identify the internal and external environment of the Purse Seine Catching Business which includes micro and macro environments and formulate alternative business development strategies for the purse seine catching business. Design/Methodology/Approach – Sampling using a questionnaire with 5 people who are experts or understand including business owners, Fishing Masters, Engineers, Marketing Department, and Boat Fishermen. Testing data analysis using the R language through Google Colab. Findings - These businesses are strong and likely, the recommendations given are Progressive, meaning that businesses are run in prime and steady condition so that it is possible to continue to expand, increase growth and achieve maximum progress. Originality/value – The added value of this research contributes to business development explaining what strategies a company should take to maximize opportunities and minimize threats